The Physical Exam An Innovative Approach in the Age of Imaging - Phillips, Raymond E. (Springer International Publishing, 2018)
This book invites clinicians to take a fresh look at the routine physical examination by outlining in detail how they can adapt a more efficient, regional approach to the exam activity. By adopting the systematic sequence and focus provided in this novel title, clinicians can offer a more modern physical examination, one that may prove more productive than the methods taught in the pre-imaging era. The Physical Exam: An Innovative Approach in the Age of Imaging offers a unique, step-by-step sequence for the physical exam. The text guides the clinician through a series of steps that involve observing, touching and listening - in an organized sequence, region by region - of all organ systems. The general approach is applicable to every physical examination and can be modified when appropriate. Express pathways are provided so that the clinicians can quickly assess the general health of the patient while focusing on the presenting problem. A major contribution to the diagnostic literature, the book offers a format and level of complexity that will be of significant value to internal medicine and family physicians, emergency professionals, nurse practitioners, physician's assistants, and medical students.